2010
DOI: 10.1111/j.1365-246x.2010.04654.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographic effects on the hill of Nocera Umbra, central Italy

Abstract: S U M M A R YDuring the M W 5.7 and 6.0 Umbria-Marche earthquakes of 1997 September 26, the historical centre of Nocera Umbra suffered MCS intensity VII-VIII. The zone is located on the top of a hill, a condition potentially favourable to ground motion amplification. However, also vulnerability is higher on the hill because of the ancient age of buildings. A temporary array of eight seismological stations was installed across the hill to quantify the amplification effect due to topography. Waveforms of 14 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 25 publications
(17 reference statements)
4
28
0
Order By: Relevance
“…The above procedure follows the work by Zevenbergen and Thorne (1987) and Moore et al (1991) and allows topographic curvature estimates at any point of the DEM. Topographic site effects for a given frequency are controlled by topographic features with characteristic sizes comparable with the associated wavelength (Geli et al, 1988;Sánchez-Sesma and Campillo, 1991;Durand et al, 1999;Buech et al, 2010;Pischiutta et al, 2010). The higher the frequency, the smaller are those features.…”
Section: Analysis Of Amplification Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above procedure follows the work by Zevenbergen and Thorne (1987) and Moore et al (1991) and allows topographic curvature estimates at any point of the DEM. Topographic site effects for a given frequency are controlled by topographic features with characteristic sizes comparable with the associated wavelength (Geli et al, 1988;Sánchez-Sesma and Campillo, 1991;Durand et al, 1999;Buech et al, 2010;Pischiutta et al, 2010). The higher the frequency, the smaller are those features.…”
Section: Analysis Of Amplification Patternsmentioning
confidence: 99%
“…The topographic site effect is a complex frequencydependent 3D phenomenon (Sánchez-Sesma, 1983;Geli et al, 1988;Sánchez-Sesma and Campillo, 1991;Bouchon and Barker, 1996;Buech et al, 2010;Maufroy et al, 2012;Massa et al, 2014) that produces large ground-motion amplifications in the vicinity of summits (Gaffet et al, 2000;Buech et al, 2010;Massa et al, 2010) and may cause damages during large earthquakes (Çelebi, 1987;Kawase and Aki, 1990;Bouchon and Barker, 1996;Spudich et al, 1996;Hough et al, 2010;Pischiutta et al, 2010). The seismic waves propagating in areas with topographies are generally disrupted at frequencies above 1 Hz (Boore, 1973;Sánchez-Sesma and Campillo, 1991;Durand et al, 1999;Pischiutta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ground motions amplify on hilltops and along ridges (e.g., Çelebi, 1987;Kawase and Aki, 1990;Bouchon and Barker, 1996;Komatitsch and Vilotte, 1998;Lee, Chan, et al, 2009), with multiple reflections prolonging seismic shaking (e.g., Lee et al, 2008). Remarkable variations in PGV and acceleration values have been attributed to topography, highlighting its role for seismic-hazard assessment (e.g., Komatitsch and Vilotte, 1998;Lee, Chan, et al, 2009; Pischiutta et al (2010), and our simulation volume features relevant topographic relief. As a consequence, inclusion of topography in our models turns out to be of fundamental importance for properly simulating observed ground motions.…”
Section: Simulations With 1d Models: Topographic Effectsmentioning
confidence: 99%
“…Using a boundary element method to investigation topographic amplification in Taiwan, Lee et al (2009) conclude that amplifications on ridges can be as high as a factor of 2. Pischiutta et al (2010) found amplification factors approaching a factor of 4 over the frequency range 2-4 Hz along a hill in central Italy with roughly comparable geometry. The amplitude, frequency, and polarization of the…”
Section: Topographic Amplificationmentioning
confidence: 83%